2001
DOI: 10.2337/diabetes.50.8.1901
|View full text |Cite
|
Sign up to set email alerts
|

Defective Insulin-Induced GLUT4 Translocation in Skeletal Muscle of High Fat–Fed Rats Is Associated With Alterations in Both Akt/Protein Kinase B and Atypical Protein Kinase C (ζ/λ) Activities

Abstract: The cellular mechanism by which high-fat feeding induces skeletal muscle insulin resistance was investigated in the present study. Insulin-stimulated glucose transport was impaired (ϳ40 -60%) in muscles of high fat-fed rats. Muscle GLUT4 expression was significantly lower in these animals (ϳ40%, P < 0.05) but only in type IIa-enriched muscle. Insulin stimulated the translocation of GLUT4 to both the plasma membrane and the transverse (T)-tubules in chow-fed rats. In marked contrast, GLUT4 translocation was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
134
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 67 publications
17
134
2
2
Order By: Relevance
“…Here we show that insulin-stimulated PKC/ activation is impaired in skeletal muscle of lipid-infused rats compared with glycerolinfused rats. Consistent with our current results are data from several insulin-resistant models including Goto-Kakizaki diabetic rats (33), high fat fed rats (67), and obese Zucker rats.…”
Section: Fig 3 Pkc/ Activities (A) and Protein Levels (B) In Musclesupporting
confidence: 80%
“…Here we show that insulin-stimulated PKC/ activation is impaired in skeletal muscle of lipid-infused rats compared with glycerolinfused rats. Consistent with our current results are data from several insulin-resistant models including Goto-Kakizaki diabetic rats (33), high fat fed rats (67), and obese Zucker rats.…”
Section: Fig 3 Pkc/ Activities (A) and Protein Levels (B) In Musclesupporting
confidence: 80%
“…Concerning the possible involvement of atypical PKC in the state of insulin resistance, insulininduced PKC-/ activation and glucose transport have been found to be profoundly decreased in skeletal muscle and adipocyte of GK rats (23,24). Along this line, insulin completely failed to activate PKC-/, regardless of only a modest decrease in insulin-induced PI 3-kinase activity in the skeletal muscle of high fatϪfed rats (25).…”
mentioning
confidence: 72%
“…7). Previous biochemical studies have found either normal (4,5) or reduced (6,37,39) overall GLUT4 content in muscle from high fat-fed animals, while GLUT4 translocation was reduced (4,5,7). One study using subcellular fractionation found completely abrogated insulin-stimulated GLUT4 translocation to both sarcolemma and T-tubules (38).…”
Section: Discussionmentioning
confidence: 99%